2006
DOI: 10.4081/ija.2006.281
|View full text |Cite
|
Sign up to set email alerts
|

Response of faba bean to phosphate fertilizer and weed control on nitisols of ethiopian highlands

Abstract: The effects of phosphorus fertilizer and weed control on yield and major yield components of faba bean (Vicia faba L.) were studied on Nitisols of Ethiopian highlands. Factorial combinations of four levels of phosphorus fertilizer (0, 10, 20 and 30 kg P ha -1 ) as triple super phosphate (TSP) and two levels of weeding (W1 = no weeding and W2 = hand weeding once six weeks after crop emergence) were laid out in randomized complete block design with three replications. Results indicated that highly significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 12 publications
(12 reference statements)
2
33
0
Order By: Relevance
“…The optimum dose of P for attaining an economic yield of field pea was found to be 20 kg ha -1 under weeded condition. A similar finding was also reported on faba bean by Getachew Agegnehu and Rezene Fessehaie (2006).…”
Section: Crop Growth and Yieldsupporting
confidence: 74%
See 2 more Smart Citations
“…The optimum dose of P for attaining an economic yield of field pea was found to be 20 kg ha -1 under weeded condition. A similar finding was also reported on faba bean by Getachew Agegnehu and Rezene Fessehaie (2006).…”
Section: Crop Growth and Yieldsupporting
confidence: 74%
“…Grain yield was most strongly correlated with plant height, number of pods per plant and total plant biomass (r = 0.59**, 0.68*** and 0.94***, respectively), which indicate that large plant height, total plant biomass and number of pods per plant are essential to high grain yield (Table 6). Similarly, Getachew Agegnehu and Rezene Fessehaie (2006) showed that grain yield of faba bean was significantly positively correlated with plant height, total biomass and number of pods per plant. The application of P fertilizer and weed control resulted in a linear response function (Fig.…”
Section: Crop Growth and Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been produced for centuries in Ethiopia and provides the much needed protein supplement to the diet of rural households. It also plays an important role in the socio-economic life of farming communities and a source of foreign currency to the country (Abebe et al, 2014, Agegnehu andFessehaie, 2006;Keneni and Jarso, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Faba bean is a major source of dietary protein (Hassan et al, 2009) and staple food used in different forms by the majority of smallscale, subsistence farmers in Ethiopia. Besides this, it plays an important role in the management of soil fertility through crop rotation in cereal production contributing to agricultural sustainability (Agegnehu and Fessehaie 2006). It is also a foreign currency earner for the national economy.…”
Section: Introductionmentioning
confidence: 99%